A critical review of the factors affecting the success of using lean to achieve green benefits - Wu, Peng; Wang, X. (2016)
Due to the rising recognition of sustainable development, various industrial sectors, including the building and construction sector, are facing increasing pressures to improve their environmental performance. The lean concept has proven to be effective in reducing waste streams and increase productivity. Many studies have therefore been conducted to link waste reduction and environmental performance improvement. A comprehensive literature review is conducted to investigate the development of integrating lean to achieve green benefits. The comprehensive literature review covers all journal articles in Scopus that have "green" and "lean" in their titles. It appears that majority of the studies within the area of lean and green focus on the conceptual framework. Very limited studies focus on the implementation of lean and green to address specific problems and provide measurable benefits. It should be noted that whether or not measurable benefits can be achieved affects the degree of implementation of lean and green at the industry level. As such, it is proposed that future studies on lean and green should be conducted and measurable benefits should be clearly articulated.